The Seventh-Grade Students’ Perception of Pictionary Game in Learning English Vocabulary at SMP N 2 Sedayu - Santi, Hesty Aris; Binawan, Herbertus (Peneliti.net, 2023)
Vocabulary is the essence of language acquisition, for first, second, and foreign languages as stated by Nurdiansyah et al., (2019). In some cases vocabulary mastery can support students to master the four English skills namely listening, speaking, reading, writing easier. However, in fact students are at a low level of vocabulary. In order to overcome this problem, it is necessary to have appropriate and active learning techniques to develop their vocabulary level . Therefore, in this study, the authors used the Pictionary game to the students. The objective of this research is to find out how students' perception of the use of a pictionary game in learning English vocabulary. This research applied qualitative research with the data obtained from observation, questionnaires, and interviews. The study was conducted at SMPN 2 Sedayu which consists of 28 students. The results of the study indicate that students had a positive perception towards the use of Pictionary games in learning English vocabulary. Pictionary games had a great impact in making learning English fun, encouraging and easy to remember some new English words.